Faktor-faktor yang mempengaruhi Nilai Waktu Uang: Future Value, Present Value, dan Annuity - Lasmarina Suci Oktavia; Lyra Aldina; Nurdiyanto Nurdiyanto; Mutia Fahrati; Tri Yulaeli (Pusat Riset dan Inovasi Nasional, 2023)
In the economy money is very important, the economy itself is the activity of managing finances and capital in order to make ends meet. In conventional economics, the term or concept of Time Value of Money is known, which simply means that money has value for the future. This concept is very useful in planning in the future. Apart from that, this concept is also often used in financial management when making decisions such as investing. on an asset and determine the source of loan funds, then understanding the time value of money is very crucial. This article reviews the factors that influence the time value of money, namely: future value, present value, annuity, and amortized loans, a study of financial management literature. The purpose of writing this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) Future value affects the time value of money; 2) Present value affects the time value of money; and 3) Annuity affects the time value of money.